2020
DOI: 10.1186/s43055-020-00272-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of multi-detector CT in analysis of the greater and lesser palatine foramina

Abstract: Background: The objective of this study was to assess variation in number, size, shape, and location of greater and lesser palatine foramina using multiple anatomical landmarks through data obtained from adult head CT scans. CT skulls of 200 adult persons were included in this study. There were 100 males and 100 females, aged from 22 to 65 years old. An e-film DICOM viewer version 2 was applied to estimate morphological parameters and to calculate the linear measurements related to the greater palatine foramen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The results of the meta-analysis regarding the distance between the greater palatine foramen and surrounding anatomical landmarks are presented in Table 4 . A total of 8 studies [ 8 , 11 , 29 , 35 , 56 , 63 , 77 , 83 ] ( n = 2358 subjects) reported data on the distance from the greater palatine foramen to the posterior nasal spine (GPF–PNS). The pooled mean, across the eight studies, was calculated to be 17.21 mm (95% CI = 16.34–18.09 mm).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the meta-analysis regarding the distance between the greater palatine foramen and surrounding anatomical landmarks are presented in Table 4 . A total of 8 studies [ 8 , 11 , 29 , 35 , 56 , 63 , 77 , 83 ] ( n = 2358 subjects) reported data on the distance from the greater palatine foramen to the posterior nasal spine (GPF–PNS). The pooled mean, across the eight studies, was calculated to be 17.21 mm (95% CI = 16.34–18.09 mm).…”
Section: Resultsmentioning
confidence: 99%
“…The studies spanned the years 1982 to 2022 and originated from Africa, Asia, Europe, North America, and South America. Thailand Cadaveric 55 Ashwini and Jaishree [7] India Cadaveric 100 Awad et al [8] Egypt Imaging 200 Ayoub et al [9] United States Imaging 50 Badshah et al [10] Pakistan Cadaveric 85 Bahşi et al [11] Turkey Imaging 150 Beetge et al [12] South Africa Imaging 77 Cagimni et al [16] Turkey Cadaveric 120 Campbell et al [17] United States Imaging 50 Cheung et al [18] China Cadaveric 30 Chopra et al [19] India Cadaveric 100 Chrcanovic and Custódio [20] Brazil Cadaveric 80 Das et al [22] United States Imaging 100 Dave et al [23] India Cadaveric 100 D'Souza et al [21] India Cadaveric 40 Douglas and Wormald [24] Australia Cadaveric 21 Duruel et al [25] United States Imaging 131 Fonseka et al [27] Sri Lanka Imaging 50 Fu et al [28] United States Cadaveric 11 Gibelli et al [29] Italy Cadaveric 100 Hassanali and Mwaniki [31] Africa Cadaveric 125 Howard-Swirzinski et al [34] United States Imaging 500 Hwang et al [35] South Korea Imaging 50 Ikuta et al [36] Brazil Imaging 50 Ilayperuma et al [37] Sri Lanka Cadaveric 136 Jaffar and Hamadah [38] Iraq Cadaveric 50 Kaffe et al [39] Israel Imaging 58 Kang et al [40] South Korea Imaging 107 Kaur et al [41] India Cadaveric 100 Klosek and Rungruang [42] Thailand Cadaveric 41 Kumar et al [43] India Cadaveric 100 Lacerda-Santos et al [44] Brazil Imaging 60 Langenegger et al [45] South Africa Cadaveric 100 Lim et al [47] South Korea Imaging 147 Lopes et al [48] Brazil Cadaveric 94 Malamed and Trieger…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 9, shows the greater palatine nerve. Morphometric parameters have been defined for the dimensions of the greater palatine foramen, which differ between male and female gender [30,31]. It may therefore be possible that similar features can be found for ultrasonographic assessment of the greater palatine A second-harmonic imaging mode SH12 was used here, with an approximately 170 µm axial resolution and 0.5 mm lateral resolution, assuming a f-number of 3.…”
Section: Casementioning
confidence: 99%